Sensorless speed drives of permanent magnet syhchronous motor using model reference adaptive control - Mustafa, Raihana (2015)
In high performance drives, speed and torque controls of permanent magnet synchronous motors are usually attained by the application of position and speed sensors. However, speed and position sensors require the additional mounting space, reduce the reliability in harsh environments and increase the cost of the motor. Therefore, many studies have been carried out and reported to eliminate the speed and position sensors such as back electromotive force, signal injection, and others. However, these techniques have the drawbacks such as sensitive to machine parameter and others. The research focuses on investigation an evaluation of the sensorless speed control of surface mounted permanent magnet synchronous motor (SMPMSM) drives controlled by PI speed controller based on MRAC combined with V-I model and reactive power model. A Model Reference Adaptive Control (MRAC) has been chosen in this research based on its simplicity, good stability, and requires less computation. The SMPMSM is controlled using the principle of rotor flux orientation. Current control is performed in rotor reference frame based on SVPWM. The drives is simulated using SIMULINK/ MATLAB and the hardware implementation is based on dSPACE (DS1103). PI speed and current controllers are at first designed and the controller parameters are manually tuned to obtain steady state stability. A detailed investigation of the varies operating points; different speed command, forward-reverse speed operation, inertia variation and different speed command profiles. The overshoot/undershoot, settling time, and rise time of the speed response are used to evaluate the controller and speed estimation methods. The simulation and experimental with MRAC combined with V-I model speed estimation method results have proved that the drives is robust to the inertia variation, load rejection properties, speed variation and different initial speed profiles. Finally, the experimental investigation in MRAC combined with V-I model speed estimation method is performed in order to confirm the theoretical findings.